Sosialisasi pemasaran produk olahan hasil hutan pada masyarakat Desa Pasar Rawa Kecamatan Gebang Kabupaten Langkat - Ferry Safriandi; Aria Masdiana Pasaribu; Windy Aginta; Ahmad Muhajir; Rafiqah Humaira; M. Afif Herliandi Nasution (Jurnal Derma Pengabdian Dosen Perguruan Tinggi (Jurnal DEPUTI), 2024)
This community service was carried out to socialize the marketing of processed forest products to the community of Pasar Rawa Village, Gebang District, Langkat Regency. The method used is by providing training. The results of this community service activity show that before the socialization was carried out, only around 40.7% of the community had knowledge of marketing techniques, whereas after the socialization was carried out, 85% had knowledge of marketing techniques. Most participants understood and were able to apply marketing techniques well. This activity ran smoothly and received a very positive response from the participants who enthusiastically participated in the event from start to finish and actively discussed issues surrounding marketing strategies for processed forest products in the community of Pasar Rawa Village, Gebang District, Langkat Regency. So this socialization supports and helps promotional techniques, providing better access to increasing people's income